Spatiotemporal Transmission and Determinants of Typhoid and Paratyphoid Fever in Hongta District, Yunnan Province, China - Wang, J.; Wang, Y.; Zhang, J.; Christakos, G.; Sun, J.; Liu, Xin; Lu, L.; Fu, X.; Shi, Y.; Li, X. (Public Library of Science, 2013)
AbstractBackground: Typhoid and paratyphoid fever are endemic in Hongta District and their prevalence, at 113 per 100,000individuals, remains the highest in China. However, the exact sources of the disease and its main epidemiologicalcharacteristics have not yet been clearly identified.Methods and Findings: Numbers of typhoid and paratyphoid cases per day during the period 2006 to 2010 were obtainedfrom the Chinese Center of Disease Control (CDC). A number of suspected disease determinants (or their proxies), wereconsidered for use in spatiotemporal analysis: these included locations of discharge canals and food markets, as well associo-economic and environmental factors. Results showed that disease prevalence was spatially clustered with clustersdecreasing with increasing distance from markets and discharge canals. More than half of the spatial variance could beexplained by a combination of economic conditions and availability of health facilities. Temporal prevalence fluctuationswere positively associated with the monthly precipitation series. Polluted hospital and residential wastewater was beingdischarged into rainwater canals. Salmonella bacteria were found in canal water, on farmland and on vegetables sold inmarkets.Conclusion: Disease transmission in Hongta district is driven principally by two spatiotemporally coupled cycles: oneinvolving seasonal variations and the other the distribution of polluted farmland (where vegetables are grown and sold inmarkets). Disease transmission was exacerbated by the fact that rainwater canals were being used for disposal of pollutedwaste from hospitals and residential areas. Social factors and their interactions also played a significant role in diseasetransmission